2015
DOI: 10.1186/s12985-015-0443-9
|View full text |Cite
|
Sign up to set email alerts
|

Quinic acid derivatives inhibit dengue virus replication in vitro

Abstract: BackgroundDengue is the most prevalent arboviral disease in tropical and sub-tropical areas of the world. The incidence of infection is estimated to be 390 million cases and 25,000 deaths per year. Despite these numbers, neither a specific treatment nor a preventive vaccine is available to protect people living in areas of high risk.ResultsWith the aim of seeking a treatment that can mitigate dengue infection, we demonstrated that the quinic acid derivatives known as compound 2 and compound 10 were effective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…An important parameter to consider is the selectivity index (SI), which ranged from 5.59 and 9.43 for the extracts or fractions. These values are similar to other reports of natural products with some anti-dengue activity [ 18 , 19 , 47 , 52 , 53 ]. SI represents the relative effectiveness of a product in inhibiting viral replication compared to inducing cell citotoxicity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…An important parameter to consider is the selectivity index (SI), which ranged from 5.59 and 9.43 for the extracts or fractions. These values are similar to other reports of natural products with some anti-dengue activity [ 18 , 19 , 47 , 52 , 53 ]. SI represents the relative effectiveness of a product in inhibiting viral replication compared to inducing cell citotoxicity.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple studies have reported the discovery or obtaining of compounds with anti-dengue properties [ 8 , 16 18 , 29 , 42 47 ], however, up to now there are no commercially available drugs for treatment of dengue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that acid derivative-containing compounds have interfered in the replicative cycle of different virus families. Zanello and coworkers showed that N-sulfonyl anthranilic acid derivatives inhibited the replication of DENV by inactivating the RNA-dependent RNA polymerase, quinic acid derivatives inhibited the replication of DENV-3 assayed using a sub-genomic replicon in RepDV3-Huh 7.5 cells 39 . Additionally, anthranilic acid derivatives were reported to act as allosteric inhibitors by binding to HCV NS5B polymerase and inhibiting viral genome replication 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, NS4b has no known enzymatic activity but is essential for replication, and is known to interact with viral and cellular proteins to form the dengue replication complex and subvert the cellular innate immune response [50]. Quinic acid derivatives were shown to reduce the amount of NS3 in treated DENV1 and DENV3 replicon-containing cells by FACS analysis [51]. Interestingly, genome replication and translation were excluded as the mode of action for some drug candidates, such as hirsutine, using the dengue subgenomic replicon system [52].…”
Section: Dengue Virus Repliconsmentioning
confidence: 99%